2000
DOI: 10.1159/000067473
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of N-Acetylcysteine on Adherence of <i>Streptococcus pneumoniae</i> and <i>Haemophilus influenzae</i> to Human Oropharyngeal Epithelial Cells in vitro

Abstract: Background: Bacterial adherence to mucosal and epithelial cell structures is of importance for the persistence of bacteria in the airways. Cigarette smoking and chronic bronchitis are associated with increased bacterial adherence. N-Acetylcysteine (NAC) medication reduces the number of infectious exacerbations in patients with chronic bronchitis, and NAC medication has been associated with low intrabronchial bacterial numbers. Objective: We investigated whether NAC influences bacterial adherence as a possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 12 publications
4
50
0
3
Order By: Relevance
“…In addition, 600 mg?day -1 NAC in COPD patients reduced sputum eosinophil cationic protein concentrations and the adhesion of PMNs [65]. In vitro, NAC reduced adhesion of Haemophilus influenzae and Streptococcus pneumoniae to oropharyngeal epithelial cells [66].…”
Section: Antioxidant and Anti-inflammatory Effectsmentioning
confidence: 99%
“…In addition, 600 mg?day -1 NAC in COPD patients reduced sputum eosinophil cationic protein concentrations and the adhesion of PMNs [65]. In vitro, NAC reduced adhesion of Haemophilus influenzae and Streptococcus pneumoniae to oropharyngeal epithelial cells [66].…”
Section: Antioxidant and Anti-inflammatory Effectsmentioning
confidence: 99%
“…Perez-Giraldo et al (32) showed that NAC reduced the formation of biofilms of Staphylococcus epidermidis on a polystyrene surface but did not distinguish between the effects on bacteria and bacterial EPS. Recently, it was shown that NAC reduced adhesion of Streptococcus pneumoniae and Haemophilus influenzae to oropharyngeal epithelial cells in vitro (36). Similarly, NAC also reduced attachment of Moraxella catarrhalis to pharyngeal epithelial cells, possibly by removing a layer of ruthenium red-positive extracellular material from the epithelial cells (49).…”
mentioning
confidence: 99%
“…N-Acetyl-L-cysteine (NAC), which is used in medical treatment of chronic bronchitis, cancer, and paracetamol intoxication (36,43), is one of the smallest drug molecules in use (28), and it has antibacterial properties. The molecule is a thiolcontaining antioxidant that disrupts disulfide bonds in mucus (3,41) and competitively inhibits amino acid (cysteine) utilization (46,50).…”
mentioning
confidence: 99%
“…Влияние на антиоксидантные системы способствует защите клеток от свободнорадикального повреждения, что приводит к снижению воспаления на слизистых оболочках дыха-тельных путей и улучшению клинической симптоматики [41]. Ацетилцистеин уменьшает адгезию патогенных бак-терий к эпителиальным клеткам слизистой оболочки дыха-тельных путей и тем самым снижает колонизацию дыха-тельных путей патогенными микробами [11,42]. Препарат приводит к уменьшению образования биопленок грам-положительными и грамотрицательными бактериями и грибами; уменьшает продукцию экстрацеллюлярного полисахаридного матрикса, что способствует разруше-нию зрелых биопленок [43][44][45].…”
Section: обзор литературыunclassified